Performance Evaluation of DSC Windows for Buildings. (21st August 2013) - Kang, Jun-Gu; Kim, Jin-Hee; Kim, Jun-Tae
Abstract : Interest in BIPV systems with dye-sensitized solar cells (DSCs) that can replace building windows has increased for zero energy buildings. Although DSCs have lower efficiency in terms of electricity generation than silicon solar cells, they allow light transmission and application of various colors; they also have low production costs, which make them especially suitable for BIPV systems. DSC research is interdisciplinary, involving electrical, chemical, material, and metal engineering. A considerable amount of research has been conducted on increasing the electrical efficiency of DSC and their modules. However, there has not been sufficient research on building applications of DSC systems. The aim of this study is to evaluate the optical performance and thermal performance of DSC windows in buildings. For this study, DSC experimental models with different thicknesses and dye colors were manufactured, and their optical properties, such as transmittance and reflectivity, were measured by a spectrometer. The thermal and optical characteristics of double-glazed windows with DSC were analyzed with a window performance analysis program, WINDOW 6.0.